The genus Rhamphothrips in India (Thysanoptera: Thripidae) with description of a new species - Tyagi, Kaomud; Kumar, Vikas (Zootaxa, 2013)
Rhamphothrips bhattii sp.n. is described from India based on specimens collected on flowers and leaves of Tabernaemontana divaricata (Apocynaceae) in the States of West Bengal and Odisha. The pronotum of this species is longer than any other known member of the genus. A key to the six species of Rhamphothrips recorded from India is provided.